2021
DOI: 10.3390/antibiotics10060687
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Infusion of β-Lactams Decreases Mortality in Patients with Septic Shock: A Retrospective before-and-after Study

Abstract: Septic shock substantially alters the pharmacokinetic properties of β-lactams with a subsequently high risk of insufficiently low serum concentrations and treatment failure. Considering their pharmacokinetic (PK)/pharmacodynamic (PD) index, prolonged infusions (PI) of β-lactams extend the time that the unbound fraction of the drug remains above the minimal inhibitory concentration MIC (ft >MIC) and may improve patient survival. The present study is a monocentric, retrospective before-and-after analysis of s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…We recently evaluated the impact of prolonged infusion in 414 severely ill patients with septic shock (mean SOFA score 13, 73% abdominal sepsis) and found a significantly lower mortality rate in patients treated with prolonged infusion. 62 After propensity score matching, mortality rates did not reach statistical significance; however, mortality rates in the prolonged infusion group were approximately 10% lower than in the intermittent bolus group. 62 The growing clinical evidence supports the preceding theoretical considerations whereby prolonged infusion and continuous infusion can mitigate critical variations in Cs by extending f T >MIC .…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…We recently evaluated the impact of prolonged infusion in 414 severely ill patients with septic shock (mean SOFA score 13, 73% abdominal sepsis) and found a significantly lower mortality rate in patients treated with prolonged infusion. 62 After propensity score matching, mortality rates did not reach statistical significance; however, mortality rates in the prolonged infusion group were approximately 10% lower than in the intermittent bolus group. 62 The growing clinical evidence supports the preceding theoretical considerations whereby prolonged infusion and continuous infusion can mitigate critical variations in Cs by extending f T >MIC .…”
Section: Resultsmentioning
confidence: 93%
“…62 After propensity score matching, mortality rates did not reach statistical significance; however, mortality rates in the prolonged infusion group were approximately 10% lower than in the intermittent bolus group. 62 The growing clinical evidence supports the preceding theoretical considerations whereby prolonged infusion and continuous infusion can mitigate critical variations in Cs by extending f T >MIC . PK optimization seems to be of special relevance for critically ill patients in the ICU and should be implemented as the standard mode of application.…”
Section: Resultsmentioning
confidence: 93%
“…A variable of interest, entitled "approach to clinical cases", was created based on the seven questions of the clinical knowledge section of the survey (question [16][17][18][19][20][21][22]. This variable was calculated by assigning a value of 1.5 to a correct answer for question 16-21 and a value of 0.1 to a correct answer for each of the ten vignettes of the 22 questions, giving a total score of 1 for this question.…”
Section: Discussionmentioning
confidence: 99%
“…With reference to β-lactam's TDM literature status, studies have shown positive results in terms of clinical cure rates (the reduction of procalcitonin in patients with TDM follow-up), a shorter mean duration of invasive ventilation, the achievement of PK parameters and an easier dose guidance process, particularly in critically ill patients or patients undergoing renal replacement therapy [7,[11][12][13][14][15][16]. More clinical studies should be developed to demonstrate the conclusive benefits of this practice.…”
Section: Introductionmentioning
confidence: 99%
“…Continuous or prolonged (to at least 40–50% of the dosing interval) application of β-lactam antibiotics were reported to cause increased (e.g., 1–4x MIC) and extended (e.g., 100% fT MIC ) blood antimicrobial drug levels compared to intermitted infusion in critically ill patients [ 20 , 21 , 22 ]. In order to avoid sub-therapeutic antimicrobial levels during a continuous or prolonged dose regime, daily TDM is highly recommended in several guidelines [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%